Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Joe Floyd Asher, Mary Beth Riday drinking, Carolyn Phillips in red, Michael Kanz, Jane Fonda seated, ?, Tom Shilton, ???